Weight status and associated factors among HIV infected people on antiretroviral therapy in rural Dikgale, Limpopo, South Africa - Felistas Mashinya; Marianne Alberts; Robert Colebunders; Jean-Pierre Van Geertruyden (AOSIS, 2016)
Background: Underweight in human immunodeficiency virus (HIV)-infected people on antiretroviral therapy (ART) complicates the management of HIV infection and contributes to mortality, whereas overweight increases the risk of cardiovascular disease (CVD). Aim: The study determined weight status and associated factors in people with HIV infection receiving ART. Setting: Rural primary health care clinics in Dikgale, Limpopo province, South Africa. Methods: A cross-sectional study in which data were collected using the World Health Organization (WHO) stepwise approach to surveillance (STEPS) questionnaire and calculated using WHO analysis programmes guide. Weight and height were measured using standard WHO procedures, and body mass index was calculated as weight (kg)/height (m2). Data on ART duration were extracted from patients' files. CD4 lymphocyte counts and viral load were determined using standard laboratory techniques. Results: Of the 214 participants, 8.9%, 54.7% and 36.4% were underweight, normal weight and overweight, respectively. Physical activity (OR: 0.99, p = 0.001) and male gender (OR: 0.29, p = 0.04) were negatively associated with overweight. Men who used tobacco were more likely to be underweight than non-tobacco users (OR: 10.87, p = 0.02). Neither ART duration nor viral load or CD4 count was independently associated with underweight or overweight in multivariate analysis. Conclusion: A high proportion of people on ART were overweight and a smaller proportion underweight. There is a need to simultaneously address the two extreme weight problems in this vulnerable population through educating them on benefits of avoiding tobacco, engaging in physical activity and raising awareness of CVD risk.